Immune T cells sorted by flow cytometry confer protection against infection with Treponema pallidum subsp. pertenue in hamsters. - Liu, H (1990)
The role of cell-mediated immunity against infection with Treponema pallidum subsp. pertenue in humans or experimental animals is unclear. Hamsters injected subcutaneously in the hind paws with 4 x 10(6) unfractionated lymph node cells or enriched lymph node T cells (immunoglobulin negative, Ia negative) from T. pallidum subsp. pertenue-immune hamsters were resistant to challenge with T. pallidum subsp. pertenue. The popliteal lymph nodes of hamsters that received immune cells weighed less and had significantly fewer treponemes than did lymph nodes from hamsters infused with cells from nonimmune donors. Furthermore, recipients of immune T cells failed to develop antitreponemal antibodies 21 days after challenge. Enriched T cells were obtained by flow cytometric separation by using monoclonal anti-Ia antibody 14-4-4s, which identified hamster B cells. Flow cytometric analysis by two-color immunofluorescent staining with anti-hamster-immunoglobulin and monoclonal anti-Ia antibody 14-4-4s confirmed that monoclonal anti-Ia antibody 14-4-4s recognized B cells. In addition, lymph node cells obtained after treatment with anti-Ia monoclonal antibody 14-4-4s and complement were 97% T cells, as determined by monoclonal antibody 20, a hamster T-cell marker. These results demonstrated that highly enriched T cells (immunoglobulin negative, Ia negative) from T. pallidum subsp. pertenue-immune hamsters conferred partial protection on hamsters against infection with T. pallidum subsp. pertenue.